Performance Analysis and Evaluation of Handover in Mobile IPv6 - Xinyi Wu; Gang Nie (2009 International Symposium on Intelligent Ubiquitous Computing and Education : 15-16 May 2009, 2009)
Mobile communication is increasingly oriented towards the usage of all IP networks as fixed network components. Handover latency in mobile IPv6 plays an important role in the performance of a given network scenario.It results in packet losses and severe end-to-end performance degradation due to throttling and retransmissions in TCP scenario. This paper present and discuss the handover process of mobile IPv6, provide an analysis of the MIPv6 handover procedure and some handover test results. The test shows that FMIPv6 can get better performance than MIPv6 in reducing handoff latency.